Finitte element analysis of knee pad - Karisma Dritanti, Maulidah Putri (2013)
Knee is so vulnerable and sensitive to alignment, a good care of knee is needed to avoid the knee from any serious injuries. Knee pad was developed to protect the knee, but still there were limitation of knowledge to find the best materials for knee pad. The purpose of this study is to study the stress distribution on the knee while wearing and without wearing knee pad. The analysis was made on the basic of the Asian’s soccer player that don’t have a history of knee injuries. Three different angle and force were applied to the knee. The result shows the knee pad helps to distribute the stress on the knee. Thus, the stress distribution on the knee pad is better on the materials that have a high young modulus. Among all the materials that has been used for analysis, it is find out that kenaf fibre is the best materials to be used in knee pad because it can distributed and absorbed more stress compared to the other materials that has been analysed